Afghanistan : mullah, Marx, and mujahid - Magnus, Ralph H.; Naby, Eden.; Rather, Dan. (Boulder, Colo. : Westview Press, 2002)
"The 2001 military campaign against the Taliban and al-Qa'ida resulted in unprecedented American interest in Afghanistan, and a plethora of instant experts arose to try to explain the country's volatile history. Magnus (who died in November 2000) and Naby are no instant experts but have expertise and extensive experience in Afghanistan, readily visible in this survey of modern Afghan history. The authors' overview of Afghanistan's complicated geography and demography is organized and well presented, as is their succinct survey of early Afghan history (from 500 BC to 1973 in less than 30 pages) -- though one wishes, given the important current role played by former king Zahir Shah, that Magnus and Naby would have told more about his four-decade rule (1933-73). Subsequent history is well narrated and accessible. The authors discuss imperialism without falling into the trap common to Western academics of blaming all of Afghanistan's woes upon foreigners. The analysis has balance and perspective. For example, they address (albeit only in passing) the Pushtun-nationalist rhetoric of successive Afghan governments in the 1950s through 1970s, a critical factor in understanding Pakistan's subsequent decision to back Islamist rather than ethnic nationalist groups in Afghanistan. Likewise, Magnus and Naby's treatment of the rise of the Taliban is well researched and balanced (and fortunately does not subscribe to the oil-company-conspiracy theories peddled by Pakistani author Ahmad Rashid in his well-known 2000 study of the Taliban). There are curious omissions in the narrative, though. Serious discussion of the United States arming of the mujahideen in the 1980s is absent, as is any serious focus on the evolution of the "Afghan Arabs," whose origins are more often than not shrouded in myth rather than reality. Usama bin Ladin is mentioned only in passing. Nevertheless, for those wishing to gain an understanding of the quagmire called Afghanistan, Magnus and Naby's book provides a good start." -- from Middle East Quarterly (Winter 2003) in www.meforum.org (Jan. 31, 2011).
Introduction -- Afghan history to 1973 -- Geopolitics then and now -- Traditional Afghan Islam -- Marx among the Afghans -- Holy warriors, Mujahidin, and fighting for Islam -- Beyond war: Afghanistan in post-cold war central Asia -- Elusive stability: Taliban, Arabs, and the Afghan future -- Appendices: A. Bibliographic essay -- B. Modern period rulers of Afghanistan -- C. Chronology of Afghan and regional events, 1747-2001.
Includes bibliographical references and index.
Keywords: Islam and politics -- Afghanistan; Communism -- Afghanistan; Afghanistan -- Politics and government